Role of nitric oxide in the local and systemic pathophysiological effects induced by Bothrops asper snake venom in mice - Teixeira, Catarina de Fátima (2006)
Objective To assess the role of nitric oxide in the most relevant local and systemic manifestations in mice injected with the venom of the snake Bothrops asper. Mice were pretreated with nitric oxide synthase inhibitors, and the modifications of the pathological effects induced by the venom were tested. Results Inhibition of NO synthesis did not affect acute local myonecrosis and hemorrhage in muscle tissue upon intramuscular injection of venom. Local footpad edema was reduced in mice pretreated with the NO synthase inhibitor L-NAME, and a reduction in the extent of inflammatory infiltrate in muscle tissue was observed after envenomation in mice pretreated with L-NAME and aminoguanidine. The most pronounced effect of NOS inhibition by L-NAME was an increment in the lethal activity of the venom, when injected by the intraperitoneal route. Conclusion Nitric oxide does not seem to play a significant role in the local acute pathological alterations (hemorrhage and myonecrosis) induced by B. asper venom in mice, although it contributes to edema and inflammatory infiltrate. Nitric oxide exerts a protective role in the systemic pathophysiological manifestations leading to lethality.